STUDY OF FREE AMINO ACIDS AND ELEMENTAL COMPOSITION OF COMMON BARLEY GRAINS AND ITS DRY EXTRACT - Pulatova, Dildora Kakhramonovna; Mamasoliev, Abrorbek Isroiljonovich; Urmanova, Flyura Faridovna; Murotov, Shokhbozmirzo Buvajon ogli (Химия растительного сырья, 2023)
The article is devoted studying of free amino acids and elemental composition of common barley grains cultivated in Uzbekistan and its dry extract. When conducting a comparative analysis of the amino acid composition of barley grains and its dry extract, their identity in qualitative composition was established – 20 amino acids, of which 8 are essential. The presence of all essential amino acids in the studied objects indicates their usefulness and high value as medicinal plant raw materials. It was found that the dry extract by the content of the sum of amino acids (7.71 mg/g) is almost 3 times higher than the grains (2.89 mg/g). But the percentage of the sum of essential amino acids from the total number of amino acids in the dry extract (20.36%) is 1.7 times less than in grains (35.29%). As a result of the conducted research in common barley grains and dry extract based on them, the presence of 41 mineral elements was found. Toxic heavy metals (As, Pb, Hg, Cd), which are subject to priority control, in the raw materials and dry extract under study are determined within the acceptable values adopted by the World Health Organization and in the State Pharmacopoeia of the Russian Federation XIII edition for medicinal plant raw materials and preparations based on it, which indicates their environmental safety. The obtained data will be in demand for the chemical characterization of raw materials and dry extract and their subsequent standardization.